2022
DOI: 10.1029/2022je007361
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Hydration Across the Southern Hemisphere of the Moon as Observed by Deep Impact

Abstract: Measurements of the 3 μm absorption feature, associated with the presence of hydroxyl and potentially molecular water, were first observed in 2009 by three separate spacecraft’ observations. Subsequent observations have revealed widespread but variable hydration over the sunlit regions of the Moon. The variability can help to disentangle the individual contributions of OH and H2O to the 3 μm absorption feature and provide insight into the mechanism of production and loss of OH/H2O on the lunar surface. We inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
5
9
0
Order By: Relevance
“…Specifically, the OMAT of SPA is also comparatively higher (Figure 2; Lemelin et al., 2022). SPA exhibits a lower hydration band depth than surrounding highland areas, consistent with previous observations that highland areas typically contain more hydration than maria (Honniball et al., 2020; Laferriere et al., 2022; McCord et al., 2011; Pieters et al., 2009; Wӧhler et al., 2017). It is currently unclear and under debate which factor, mineral abundance or OMAT, dominates the hydration content.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Specifically, the OMAT of SPA is also comparatively higher (Figure 2; Lemelin et al., 2022). SPA exhibits a lower hydration band depth than surrounding highland areas, consistent with previous observations that highland areas typically contain more hydration than maria (Honniball et al., 2020; Laferriere et al., 2022; McCord et al., 2011; Pieters et al., 2009; Wӧhler et al., 2017). It is currently unclear and under debate which factor, mineral abundance or OMAT, dominates the hydration content.…”
Section: Discussionsupporting
confidence: 87%
“…However, comparison of repeat In‐Magnetotail and Out‐Magnetotail mosaics showed that there is no obvious hydration content variation between the Moon is in and outside the magnetotail. This observation seems to support the migration mechanism (Hendrix et al., 2019; Laferriere et al., 2022). However, Wang et al.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The presence of localized enhancements in water abundance may support the hypothesis that at least part of the water produced by solar wind and meteoroid bombardment on the lunar surface may subsequently migrate toward the poles (Schorghofer et al 2017;Hendrix et al 2019), that localized topography and roughness may play a role in water retention on the lunar surface (Davidsson & Hosseini 2021), and that colder portions of the polar regions may retain water even if not permanently shadowed (Kloos et al 2019;Hayne et al 2021). Both the observations from Deep Impact (Sunshine et al 2009;Laferriere et al 2022) and SOFIA show higher H 2 O abundances where the surface is locally colder, and where migrating water may collect in cold traps and be reduced at high temperature on a diurnal cycle. The observational results presented in this paper pertain to the distribution of water traced by the 6.1 μm emissivity feature, which arise from water molecules very near the surface but could trace a more pervasive source.…”
Section: Discussionmentioning
confidence: 63%